EVALUASI GOOD GOVERNANCE DALAM UPAYA MENINGKATKAN PARTISIPASI MASYARAKAT DI DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) STUDI KASUS MUSRENBANG DESA TEGAL KERTHA, KOTA DENPASAR - Mahadi, Lalu Arman; Noak, SH.,M.Si, Dr. Piers Andreas; Dwi W, SE., M.AP, Kadek Wiwin (CITIZEN CHARTER, 2015)
ABSTRACT Village development planning or commonly called village Musrenbang is an annual forum for stakeholders both from the government, private sector, and from the general public to discuss the development in their village. However, the process and the implementation planning forums at village level is not in accordance with what has been announced by the central government, Musrenbang happened only as a formality to meet the agenda of the annual work program without directly involving public participation, as it happens in Tegal Kertha village, the city of Denpasar. Looking at the problem, the purpose of this study is the evaluation of the implementation Musrenbang at the village level and also to determine what factors causing low levels of citizen participation in village Musrenbang. This study used a qualitative descriptive method to obtain the data, researchers conducted by direct observation to occured the phenomenon in the field and conduct in-depth interviews to informant that related with the implementation of village Musrenbang in tegal Kertha village, Denpasar. The conclusion of this research is the level of public participation is still very low in the process of implementation of village Musrenbang in tegal kertha is due to a lack of good information about the process of Musrenbang itself to the public and also the lack of binding rules that are applied directly from the central goverment or in accordance with the constitution so the stakeholders implemented the annual program just as a formality to meet the program works without involving the direct public participation of the community. Keywords : village Musrenbang, public participation, Good Governance